Respiratory sequelae and quality of life in children one‐year after being admitted with a lower respiratory tract infection: A prospective cohort study from a developing country. Issue 2 (17th December 2019) - Nathan, Anna M.; Teh, Cindy S.J.; Eg, Kah Peng; Jabar, Kartini A.; Zaki, Rafdzah; Hng, Shih Ying; Westerhout, Caroline; Thavagnanam, Surendran; de Bruyne, Jessie A.
Abstract: Introduction: Respiratory tract infections in children can result in respiratory sequelae. We aimed to determine the prevalence of, and factors associated with persistent respiratory sequelae 1 year after admission for a lower respiratory tract infection (LRTI). Methodology: This prospective cohort study involved children 1 month to 5‐years‐old admitted with an LRTI. Children with asthma were excluded. Patients were reviewed at 1‐, 6‐, and 12‐months post‐hospital discharge. The parent cough‐specific quality of life, the depression, anxiety, and stress scale questionnaire and cough diary for 1 month, were administered. Outcomes reviewed were number of unscheduled healthcare visits, respiratory symptoms and final respiratory diagnosis at 6 and/or 12 month‐review by pediatric pulmonologists. Results: Three hundred patients with a mean ± SD age of 14 ± 15 months old were recruited. After 1 month, 239 (79.7%) returned: 28.5% (n = 68/239) had sought medical advice and 18% (n = 43/239) had cough at clinic review. Children who received antibiotics in hospital had significantly lower total cough scores ( P  = .005) as per the cough diary. After 1 year, 26% (n = 78/300) had a respiratory problem, predominantly preschool wheezing phenotype (n = 64/78, 82.1%). Three children had bronchiectasis or bronchiolitis obliterans. The parent cough‐specific quality of life (PCQOL) was significantly lower in children with respiratory sequelae ( P  < .01). In logistic regression, the use of antibiotics in hospitals (adjusted odds ratio, 0.46; P  = .005) was associated with reduced risk of respiratory sequelae. Conclusion: In children admitted for LRTI, a quarter had respiratory sequelae, of which preschool wheeze was the commonest. The use of antibiotics was associated with a lower risk of respiratory sequelae.